"They just put me in a box of all Black people in the United States:" A Mixed-Methods Exploration of Ethnic and Racial Identity, Critical Consciousness, and Health Outcomes among Black Immigrant Adolescents - Goncalves, Carolina. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Child Development.; Advisor: Ellen Pinderhughes.; Committee: Richard Lerner, Sasha Fleary, and Deborah Johnson.; Keywords: Developmental psychology, Psychology, and Public health.